Lipid-induced up-regulation of human acyl-CoA synthetase 5 promotes hepatocellular apoptosis - Reinartz, Andrea; Ehling, Josef; Leue, Andrea; Liedtke, Christian; Schneider, Ursula; Kopitz, Jürgen; Weiss, Thomas; Hellerbrand, Claus; Weiskirchen, Ralf; Knüchel, Ruth; Gassler, Nikolaus (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2010)
In the pathogenesis of nonalcoholic fatty liver disease, accumulation of lipids in hepatocytes and hepatocyte apoptosis are strongly implicated in disease progression from the potentially reversible condition of steatosis to severe acute and chronic liver injury. Acyl-CoA synthetase 5, a member of the ACSL gene family that catalyzes the activation of long-chain fatty acids for lipid biosynthesis, is the only ACSL isoform that is both, located on mitochondria and functionally involved in enterocyte apoptosis. In this study, the regulation of human ACSL5 in hepatocellular fatty acid degeneration and its involvement in hepatocyte apoptosis was investigated using models of in vitro and in vivo steatosis as well as plasmid-mediated stable gene transfer and RNAi-mediated gene silencing. ACSL5 mRNA and protein were strongly increased by uptake of dietary derived fatty acids in primary human hepatocytes, HepG2 cells and human steatotic liver. Over-expression of ACSL5 decreased HepG2 cell viability and increased susceptibility to TRAIL- and TNFα-, but not FAS- induced apoptosis, whereas knock down of ACSL5 reduced apoptosis susceptibility. High ACSL5 activity resulted in enhanced caspase-3/7 activity, but was not accompanied by up-regulation of death receptors, DR4, DR5 or TNF-R1. This study gives evidence that hepatocyte steatosis is associated with ACSL5 up-regulation resulting in increased susceptibility to hepatic cell death. We propose that ACSL5 could play a role in promoting fatty acid-induced lipoapoptosis in hepatocytes as important mechanism in fatty liver-related disorders.
Gesehen am 12.05.2023